The global market demand for Philippine bamboo - Fulgar, JC Jaf O.; Gomez, Aurelia Luzviminda V.
This study was conducted to determine the international demand for the Philippine bamboo and bamboo products. The analysis made use of secondary data obtainable from the INBAR Trade Database and the UN ComTrade Database. Descriptive analysis, as well as regression analysis and growth rates, was applied in order to determine the global scenario of the bamboo industry for the years 2007 and 2012, factors affecting export demand , export demand and import substitution of Philippine bamboo. Results show that Philippines imported bamboo flooring, shoots, plywood, and mats and screens the most, while its top exports were bamboo and rattan seats and furniture, and bamboo basketwork and wickerwork. It was found out that the biggest market for Philippine bamboo products were those in the US and Europe. Moreover, changes in export demand in the US market for Philippine bamboo products were driven by the export prices in China and the foreign exchange rate between peso and dollar. In the EU market, however , there were no significant factors. Import substitution by the Philippines had decreasing growth rates, while export demand growth rates varied per product. Given the results, it is concluded that there is a global market demand for Philippine bamboo products -except, however, for bamboo pulp and bamboo charcoal -and in order to take advantage of this demand, the government should continue there initiatives of establishing bamboo production plants as well as improve studies on bamboo and bamboo production.
Thesis, Undergraduate (BS Agribusiness Economics)--University of the Philippines, Mindanao
Keywords: Philippine bamboo